Toward combined local-average stress field modeling of reinforced concrete. (15th March 2016) - JahanMohammadi, Atefeh; Soltani, Masoud
Highlights: Local mechanisms are investigated in determination of total response of RC members. A slip–strain relation is proposed to determine the strain distribution on rebar. A post-process procedure is proposed to locally enhance the smeared crack approach. Averaged smeared models are improved in the presence of local mechanisms. Nonlinear finite element program (ESMARC) is developed for analysis of RC members. Abstract: Local mechanisms in RC domain are highly related to cracking initiation/propagation and reinforcement arrangement. These mechanisms and their significant role in the determination of average constitutive models are investigated in this paper. Developing a FORTRAN-based nonlinear finite element program, effects of changing local mechanisms' state during loading procedure are introduced into average tension-softening/stiffening behavior of concrete and average yield strength of steel bar. Adopting a "post-process" procedure, a combined local-average finite element modeling of RC members is conceivable. Accordingly, adequate displacement values are detected at the crack plane and accurate displacement-based constitutive models are applied instead of simplified strain-based ones.